Program Makan Bergizi Gratis (MBG) dalam Perspektif Keadilan Sosial dan Dinamika Sosial – Politik - Anif Kiftiyah; Firda Ayu Palestina; Faris Ulul Abshar; Khofidotur Rofiah (Badan Pembinaan Ideologi Pancasila, 2025)
Makan Bergizi Gratis (MBG) is a flagship program of the Prabowo Subianto-Gibran administration. One of the program's objectives is to improve the welfare of society, particularly students. However, the implementation of the MBG program has raised many criticisms and questions. This study will examine whether the program is on target, thereby providing equitable welfare and social justice in line with the implementation of the fifth principle of Pancasila, as well as the implementation of the MBG program from a socio-political dynamics perspective. The purpose of this study is to examine the dynamics of the MBG program's implementation from the perspective of social justice and socio-political dynamics. This study is expected to contribute to providing input for the implementation of the MBG program from the perspective of